Thermodynamic parameters optimization of an aviation three-shaft turbofan engine with an intercooler and a recuperator under flight condition. Issue 1 (May 2021) - Omar, H H; Kuz'michev, V S; Tkachenko, A Y
Abstract: The use of heat recovery in turbofan engines to improve their efficiency is not so obvious. Installing a recuperator behind the turbine of the main engine duct to heat the air at the entrance to the combustion chamber, on the one hand, reduces fuel consumption, but on the other hand, leads to a decrease in the temperature at the entrance to the jet nozzle of the main duct, thereby reducing the gas flow rate from the nozzle and, consequently, the specific thrust and thrust of the engine as a whole. The installation of an intercooler for intermediate cooling of the air between compressors allows to reduce the net-work and power of the high-pressure compressor and increase the gas pressure behind the turbine, and, consequently, the speed, specific thrust, and thrust of the engine. However, the amount of possible gain in the efficiency of a turbofan engine due to heat recovery will depend on how well the parameters of the working process of the engine and heat exchanger are selected. And this can be done only by optimizing these parameters in terms of evaluating the efficiency of the engine in the aircraft system. The article presents the results of optimizing the parameters of the working process of three-shaft turbofan engines with an intercooler and a recuperator in the system of a passenger aircraft of the Boeing 737 MAX 7 according to such criteria as the total weight of the power plant and the fuel required for the flight, and the specific fuel consumption of the aircraft per ton-kilometer of the transported commercial load.